2022
DOI: 10.3390/biomedicines10061372
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of DNA Methylation Pattern in Myotonic Dystrophy Type 1 Samples Reveals a Distinct DNA Methylation Profile between Tissues and a Novel Muscle-Associated Epigenetic Dysregulation

Abstract: Myotonic dystrophy type 1 (DM1) is a progressive, non-treatable, multi-systemic disorder. To investigate the contribution of epigenetics to the complexity of DM1, we compared DNA methylation profiles of four annotated CpG islands (CpGis) in the DMPK locus and neighbouring genes, in distinct DM1 tissues and derived cells, representing six DM1 subtypes, by bisulphite sequencing. In blood, we found no differences in CpGi 74, 43 and 36 in DNA methylation profile. In contrast, a CTCF1 DNA methylation gradient was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(85 reference statements)
0
3
0
Order By: Relevance
“… 10 , 11 , 12 In addition, our group also demonstrated that the CTCF1 region was methylated in a tissue-specific manner only in DM1 muscle biopsies (and not in skin or blood from the same patients), as well as in primary DM1 muscle cells, whereas tissues from unaffected individuals were completely unmethylated. 12 Importantly, the DM1 immortalized muscle cells showed the previously reported CTCF1 hypermethylation in both myoblasts (muscle progenitor cells) and myotubes (mature muscle cells), indicating that the DNA methylation alterations were conserved. However, we observed a significant difference in the methylation levels between primary and immortalized cell lines.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“… 10 , 11 , 12 In addition, our group also demonstrated that the CTCF1 region was methylated in a tissue-specific manner only in DM1 muscle biopsies (and not in skin or blood from the same patients), as well as in primary DM1 muscle cells, whereas tissues from unaffected individuals were completely unmethylated. 12 Importantly, the DM1 immortalized muscle cells showed the previously reported CTCF1 hypermethylation in both myoblasts (muscle progenitor cells) and myotubes (mature muscle cells), indicating that the DNA methylation alterations were conserved. However, we observed a significant difference in the methylation levels between primary and immortalized cell lines.…”
Section: Discussionmentioning
confidence: 64%
“…Epigenetics may have a role in DM1, as the CTG expansion overlaps with a 3.5 kb CpG island. 10 , 11 , 12 , 13 The DMPK gene is in chromosome 19q surrounded by the DMWD (upstream) and SIX5 (downstream) genes. The DMPK locus contains several CpG islands, including the CTCF1 and CTCF2 regions, which are surrounding the CTG expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation